Age, Virility and Vernacularity: Boccaccio's Portraits of the Artists as Young Men. (3rd July 2019) - Díaz, Sara E.
ABSTRACT: This article explores discourses of youth and maturity in the pseudo-autobiographical frames to Boccaccio's own works, and in his biographies of Dante and Petrarch. It analyses paradigmatic approaches to authorial age and their movement towards and away from an erotic literary past. These age tropes are contextualised by surveying the chronological limits, characteristics and values ascribed in the Middle Ages to phases of the masculine lifespan. The article then discusses self-reflexive narratives of authorial maturation in several works by the Tre corone that are in dialogue with each other: Boccaccio's Vita Petracchi and Petrarch's Ad Posteritatem ; Boccaccio's Trattatello and Dante's various io- personae ; alongside Boccaccio's own contradictory first-person portraits in different narrative levels of the Decameron, and his parodic Lover-Narrator in the Corbaccio . Ultimately, this study shows how, by different routes, Boccaccio breaks away from Petrarchan exemplarity by pairing vernacularity with mature philogyny, thus forging a separate path for vernacular authorship.